STUDI TENTANG PENANAMAN MODAL ASING DI INDONESIA - Ambarsari, Indah; Purnomo, Didit (Universitas Muhammdaiyah Surakarta, 2005)
Investment as one of crucial production factor, plays a big role in increasing production as shown through economic growth. In other words, investment becomes a shift variable or a loco of national economic activities.During 1980 until 2002,the investment both PMDN and Foreign Direct Investment (PMA) has grown rapidly. This investment growth especially PMA growth, besides supported by regulation and debureaucratisation which has done by the government, the demand to invest their capital is determined by macroeconomic variables, i.e. Indonesia Gross Domestic Product (GDP), SBI interest rate, domestic deposit interest rate, LIBOR interest rate, and US dollar exchange rate.By using regression analysis with error correction method (ECM), this study will explore the behaviour of several macroeconomic variables on PMA in Indonesia.